An evaluation of the Health Library Documentation and Information Network (HELDIN) in Indonesia implications for future development of the system - Lumatauw, Kayes (1986)
The aim of this study is to evaluate the present status of the HELDIN system, and to determine how well the system is attaining its functions and programmes. The study tries to identify the strengths and weaknesses of the HELDIN system in order to formulate a more effective plan for the future. It was designed and carried out in December 1985 up to April 1986.